Hearing loss and type 2 diabetes: is there a link?. (November 2014) - Morrison, CL; Morar, P; Morrison, G; Purewal, TS; Weston, PJ
Abstract Recent meta‐analysis has confirmed an association between hearing loss and diabetes. The cause remains uncertain and open to academic debate. This five‐year retrospective study examined the outcomes of patients referred for audiological investigations from a large primary care diabetes clinic. Audiological assessment included pure‐tone audiometry, and the presence of neuropathy was identified by foot examination and risk stratification. Referral rates of patients with diabetes were nearly twice those seen in the non‐diabetic population (7.5% [107/1428] vs 4% [499/12422]). Hearing loss was identified in 77 patients. The majority (84.1%) had high‐frequency sensorineural hearing loss. Loss of protective sensation on the 10 g monofilament test (OR 3.2, CI 1.6–6.5) and vibration sense (OR 2.6, CI 1.2–5.6) was significantly higher in the hearing loss group when compared with a group with type 2 diabetes and normal hearing (n = 219). The hearing loss group had almost twice the rate of at‐risk feet (37.7% vs 20.1%); (OR 2.4, CI 1.4–4.2). Pre‐existing cardiovascular disease was the only pre‐morbid condition that was associated with hearing loss (OR 1.8, 95% CI 1.1–3.2). There were no differences in HbA1c and lipids. This is the first study from primary care to show that hearing loss is prevalent and has a strong association with peripheral neuropathy. There are no effective strategies yet identified that can prevent or reverse diabetes‐related hearing loss. Clinicians should recognise the association between diabetes and hearing loss, and engage in preventative health education and hearing conservation strategies. Copyright © 2014 John Wiley & Sons, Ltd.